2, 5‐Dihydroxybenzoic acid solution in MALDI‐MS: ageing and use for mass calibration. (29th September 2014) - Teearu, Anu; Vahur, Signe; Haljasorg, Uku; Leito, Ivo; Haljasorg, Tõiv; Toom, Lauri
<x xml:space="preserve">Abstract</x> 2, 5‐Dihydroxybenzoic acid (DHB) is one of the most widely used and studied matrix compounds in matrix‐assisted laser desorption/ionization (MALDI) mass spectrometry. However, the influence of ageing of the DHB solution on the MALDI mass spectra has not been yet systematically studied. In this work, the possible changes occurring in the acidified acetonitrile/water solution of the MALDI matrix compound DHB during 1‐year usage period have been monitored with MALDI‐Fourier transform ion cyclotron resonance mass spectrometer (MALDI‐FT‐ICR‐MS) and attenuated total reflectance Fourier transform infrared (ATR‐FT‐IR) spectroscopy. No significant ageing products have been detected. The ability of the aged DHB solution to act as a MALDI matrix was tested with two materials widely used in art and conservation – bone glue (a proteinaceous material) and shellac resin (a resinous material) – and good results were obtained. A number of peaks in the mass spectra measured from the DHB solution were identified, which can be used for internal calibration of the mass axis. Copyright © 2014 John Wiley & Sons, Ltd.